Calico bush - Field, Rachel, 1894-1942 (Macmillan, 1966)
In 1743, thirteen-year-old Marguerite Ledoux travels to Maine as the indentured servant of a family that regards her as little better than the Indians that threaten them, but her strength, quick thinking and courage surprise them all.